Communication of the victim in the criminal proceedings of Ukraine in the conditions of martial law - Rakipova, Inna; Podobnyi, Oleksandr; Smirnov, Maksim; Ulianov, Oleksiy; Chipko, Nataliia (DIXI, 2023)
The article examines the doctrinal understanding of the concept of ‘communication’ in criminal procedural law. It was concluded that communication in the criminal process (criminal-procedural communication) is an end-to-end exchange of information, which is characteristic of the criminal-procedural communicative space of both law-making and law-enforcement spheres. In a broad sense, it consists in law enforcement (judicial, doctrinal) interpretation before, during and after the application of the criminal procedural norm. In a narrow sense, this is the exchange of procedurally significant information by the participants of criminal procedural activities between themselves and the court in connection with the progress of criminal proceedings. Such an exchange consists in the provision of information, joint participation in the conduct of procedural actions and their mutual perception of each other, which is implemented in the procedural forms provided for by law. It is noted that the implementation of criminal proceedings in the conditions of martial law in Ukraine reinforces the relevance of the problem of the victim’s communication. It also requires the creation of human rights sectoral mechanisms that would ensure the protection of the victim’s rights. In particular, regarding compensation for damage caused to him/her as a result of criminal offenses due to the conduct of military operations on the territory of Ukraine. It is emphasized that the reloading of the ‘image of the victim’ in criminal procedural law should take place on the basis of the victim-centered approach proposed by the Advisory Mission of the European Union in Ukraine.